Intellectual Displacement in Architectural Text Hayder Aliyve Cultural Center in Baku - As Case Study (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This current paper tries to discuss the intellectual displacement mechanics, and how subjects fragmented and became multiple, then the vision will be clear to the receivers to weave the plot regarding the intellectual vision of the designer and his recognition of the event inside the social system and transfer it to intellectual symbolic system which knowledge can be generated. This article explores how to embody displacement in Intellectual space in the contemporary Architecture and reach balance regarding the Intellectual assignment through remembering. Also, knowing the intellectual space displacement in the Architectural text throughout roots creation in the design process. The goal of this paper was determined to achieve an Architectural space formula with intellectual by searching of intellectual displacement operation in intellectual space., and presenting the changes that occur in the Architectural text regarding this concept. This paper has found, that the intellectual displacement strategy opened a vision in front of the receiver with intellectual fabrication and its cultural language using its denotations, because it makes the receiver to leave his narrowing materiality vision and goes in a textual structure moves the solids, interrogates the noiselessness and assign acts to things before individuals through relying on the intellectual displacement strategy to create the intellectual space.